Orwell and Huxley: Making Dissent Unthinkable - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2002)
In this paper I compare the fictional world depicted by Orwell’s 1984 with that of Huxley’s Brave New World from the point of view of an analytic philosopher. Neither novel should be read as predictions, the accuracy of which can be used to judge them. Rather, both attempt to portray what humanity could conceivably become. The authenticity of this conceivability is a necessary condition of the power of both works to raise central philosophical questions about the human condition. What is ethically wrong with control? How far can Man go in recreating himself? In what sense are these worlds anti-utopian? Are they really possible worlds? How credible are they as political systems? In what ways do the different systems depict the end of humanity? What logical and moral objections could be made against their fictional apologists?